A importância das plantas e dos herbívoros hospedeiros na especialização dos parasitoides de afídeos - Bergamo, Norem Ceane da Silveira Barbosa (2021)
The variety of host organisms represents one of the most important dimensions of the ecological niche of parasitoids and parasites in general. In the case of insect parasitoids that attack herbivores, the degree of specialization of these in the use of hosts can be determined by cues and restrictions imposed by herbivores and by their host plants. We used plant-aphid-parasitoid interactions sampled from several regions of the globe to investigate the specialization in the use of aphids and plants by parasitoid. Specifically, we aim to answer the following questions: (1) which trophic level, plants or herbivores, exerts greater influence on parasitoid specialization? (2) how important is the scale of network, regional or global, for specialization patterns? We found phylogenetic specialization of the parasitoids toward both aphids and plants, with specialization toward aphids being greater when compared to specialization toward plants. As for the effect of spatial scale, specialization was more evident when evaluated on a global scale than on a regional scale, especially for plants. These results reinforce the importance of coevolutionary history in the interactions between parasitoids and aphids, and also demonstrate the mediation role of plants in determining the interactions between parasitoids and host herbivores.